Efforts to improve the economy of rural communities through the development of Banjarandap tourism management strategies - Dwi Winarni; Naelati Tubastuvi; Rhis Ogie Dewandaru (Community Empowerment, 2022)
Tourism development requires strategic management in order to improve the economy of the community. The same commitment and vision must be shared by all managing institutions, including tourism awareness groups, village-owned enterprises, youth organizations, and village governments. Institutional management, potential mapping, financial management that has not been systemized, and the lack of a marketing strategy and long-term tourism sustainability are some of the challenges in pioneering and developing Banjarandap tourism. As a result, efforts have been made to establish an institutional structure, the formation of a vision and mission, potential mapping, licensing of tourist sites, management of tourism development strategies, financial management training and assistance, marketing training and assistance, and long-term sustainability through the use of technology. The contributions and benefits obtained by partners and the community are improving the quality of sustainable village tourism management, improving socio-economic conditions, improving morals and character, as well as community education through mutual cooperation and mutual concern for welfare and peace in Banjaran Village.